A Study in Red: The Overlooked Role of Azo‐Moieties in Polymeric Carbon Nitride Photocatalysts with Strongly Extended Optical Absorption. Issue 68 (21st October 2021) - Mitoraj, Dariusz; Krivtsov, Igor; Li, Chunyu; Rajagopal, Ashwene; Im, Changbin; Adler, Christiane; Köble, Kerstin; Khainakova, Olena; Hniopek, Julian; Neumann, Christof; Turchanin, Andrey; da Silva, Ivan; et al.
Abstract: The unique optical and photoredox properties of heptazine‐based polymeric carbon nitride (PCN) materials make them promising semiconductors for driving various productive photocatalytic conversions. However, their typical absorption onset at ca. 430–450 nm is still far from optimum for efficient sunlight harvesting. Despite many reports of successful attempts to extend the light absorption range of PCNs, the determination of the structural features responsible for the red shift of the light absorption edge beyond 450 nm has often been obstructed by the highly disordered structure of PCNs and/or low content of the moieties responsible for changes in optical and electronic properties. In this work, we implement a high‐temperature (900 °C) treatment procedure for turning the conventional melamine‐derived yellow PCN into a red carbon nitride. This approach preserves the typical PCN structure but incorporates a new functionality that promotes visible light absorption. A detailed characterization of the prepared material reveals that partial heptazine fragmentation accompanied by de‐ammonification leads to the formation of azo‐groups in the red PCN, a chromophore moiety whose role in shifting the optical absorption edge of PCNs has been overlooked so far. These azo moieties can be activated under visible‐light (470 nm) for H2 evolution even without any additional co‐catalyst, but are also responsible for enhanced charge‐trapping and radiative recombination, as shown by spectroscopic studies. Abstract : What makes it red ? A novel high‐temperature treatment procedure for turning the conventional melamine‐derived yellow polymeric carbon nitride into a red carbon nitride is reported. Surprisingly, a detailed characterization reveals that the red colour comes from the azo‐groups formed during the synthesis, a moiety whose role in shifting the optical absorption edge and photocatalytic activity of carbon nitrides more into the visible range has been overlooked so far.